2020
DOI: 10.1253/circj.cj-19-0856
|View full text |Cite
|
Sign up to set email alerts
|

Osborn Wave Is Related to Ventricular Fibrillation and Tachycardia in Hypothermic Patients

Abstract: Background: The Osborn wave (OW) is often observed in hypothermic patients; however, whether OW in hypothermic patients is related to the development of fatal ventricular arrhythmia, including ventricular fibrillation (VF) and pulseless ventricular tachycardia (VT), remains undetermined. This study aimed to estimate the association between OW and the incidence of fatal ventricular arrhythmias. Methods and Results: This retrospective study used the Japanese Accidental Hypothermia Network registry database and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Hypothermia is an important trigger of ventricular tachyarrhythmias, particularly ERS but not BrS. Thus, in patients with J waves mainly due to delayed conduction, and even in patients without J waves, other factors such as QT interval on ECG and serum potassium level should be carefully monitored and corrected [ 6 , 7 ]. Isoproterenol, a β-adrenergic agonist capable of augmenting I Ca,L , reduces the amplitude of the J wave and prevents arrhythmogenesis associated with JWS by opposing the increased outward current forces [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia is an important trigger of ventricular tachyarrhythmias, particularly ERS but not BrS. Thus, in patients with J waves mainly due to delayed conduction, and even in patients without J waves, other factors such as QT interval on ECG and serum potassium level should be carefully monitored and corrected [ 6 , 7 ]. Isoproterenol, a β-adrenergic agonist capable of augmenting I Ca,L , reduces the amplitude of the J wave and prevents arrhythmogenesis associated with JWS by opposing the increased outward current forces [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias associated with JWS, hypothermia, and the acute phase of ST-segment elevation myocardial infarction are mechanistically linked to abnormalities in the manifestation of I to -mediated J waves [ 3 ]. On the other hand, ventricular tachyarrhythmias during hypothermia, which occur only in cases with J waves, do not increase mortality; however, once VF has occurred, it is often fatal [ 7 ]. The incidence of VF is unexpectedly low in hypothermic patients with J waves, varying from 0% to 2% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, previous studies have suggested that hypothermia can reduce cardiovascular stability, prolong the QT interval, and induce VF/VT. 17,18 Defibrillation plays a key role in the treatment of VF/VT, aiming to restore a 'normal' cardiac rhythm and provide car- 528 diac output to some extent, although there is no consensus on the need of defibrillation in patients on VA-ECMO. Defibrillation may any increase myocardial injury during VA-ECMO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) In the present study, all ECPR patients were treated with mild hypothermia, with a body temperature between 33°C and 35°C, while RCS patients only needed fever control and generally maintained a body temperature < 37°C. Incidentally, previous studies have suggested that hypothermia can reduce cardiovascular stability, prolong the QT interval, and induce VF/VT 17,18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation